Size and household use area for a group of wild Callithrix Jacchus (PRIMATES CEBIDAE: Callitrichinae) on state park Dois Irmãos, Recife-PE - Albuquerque, Juliana Ribeiro de; Silva, Julianne Moura da; Oliveira, Maria Adélia Borstelmann de; Silva, Valdir Luna da (Revista Nordestina de Zoologia, 2012)
The genus Callithrix is composed with species adaptable to a variety of environments, which should supply your diet and reproduction, these needs are directly involved in the spatial dynamics in the pattern of activities of animals. A group of Callithrix jacchus was monitored from May 2009 to February 2010 in the Parque Estadual Dois Irmãos, Recife, State of Pernambuco. The method applied for data collection was the instantaneous scan, the materials used for behavioral records were ethogram and tokens scan and GPS to obtain the home range size. The most common activities were included in the "stationary", the home range size reached 4.7ha and its use was variable, depending on the availability of food, the seasons, the dynamics population and interactions with visitors and other animals in the park.